THE CURSED QUEEN - Fine, Sarah (New York : Margaret K. McElderry Books, 2018)
"Ansa has always been a fighter. As a child, she fought the invaders who murdered her parents and snatched her as a raid prize. She fought for her status as a warrior in her tribe, but the day the Krigere cross the great lake and threaten the witch queen of the Kupari, everything changes"-- Provided by publisher.
Keywords: American fiction; Fantasy -- Juvenile fiction; Kings, queens, rulers, etc. -- Juvenile fiction; War -- Juvenile fiction